Pemaknaan Poster Iklan layanan Masyarakat Pemilihan Umum 2024 - Silaban, Donna Isra; Riang, Yoseph; Bouk, Hendrikus Saku; Da Rato, Melva Margareth Canalini; Medilmana, Oktafiana (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2025)
This research aims to analyze the meanings contained in the public service advertisement posters for General Election 2024 using Roland Barthes' semiotic approach. Semiotics, as the study of signs and symbols and their use, is highly relevant in designing effective advertising posters. Using a descriptive qualitative method, this research explores the denotation, connotation and mythical meanings hidden behind the visual elements of the poster. The results show that the denotation meaning is displayed through visual elements such as the color of the ballot papers, the KPU logo, and the images of candidate pairs that are clear and easy to understand. The connotation meaning in the poster reflects deeper values and touches the emotional aspects of society. Visual elements such as dynamic design, the use of bold but harmonious colors, and the representation of candidate pairs who appear confident, thus illustrating a sense of responsibility as citizens to participate in elections. Meanwhile, the mythical meanings in the posters reflect narratives about democratic values, hope for change, and national stability, which evoke a sense of togetherness and optimism among the people.